Nonequilibrium charge dynamics in organic solar cells - Howard, Ian A.; Etzold, Fabian; Laquai, Frédéric; Kemerink, Martijn (Advanced energy materials, 2014)
The dynamics of charge carriers after their creation at, or near, an interface play a critical role in determining the efficiency of organic solar cells as they dictate, via mechanisms that are not yet fully understood, the pathways for charge separation and recombination. Here, a combination of ultrafast transient spectroscopy and kinetic Monte Carlo simulations based on a minimalistic model are used to examine various aspects of these charge dynamics in a typical donor-acceptor copolymer:methanofullerene blend. The observed rates of charge carrier energetic relaxation and recombination for a sequence of charge densities can be all consistently described in terms of the extended Gaussian disorder model. The physical picture that arises is a) that initial charge motion is highly diffusive and boosted by energetic relaxation in the disordered density of states and b) that mobile charge carriers dissociate from and re-associate into Coulombically associated pairs faster than they recombine, especially at early times. A simple analytical calculation confirms this picture and can be used to identify sub-Langevin recombination as the cause for quantitative deviations between the Monte Carlo calculations and the measured concentration dependence of the charge recombination.
Gesehen am 12.12.2019